A utilização da terapia do sandplay no tratamento de crianças com transtorno obsessivo-compulsivo - Matta, Reinalda Melo da (2006)
The objective of this study is to present the results from using sandplay therapy to treat three children between the ages of 6 and 9, who received a psychiatric diagnosis of obsessive-compulsive disorder. This psychopathology occurs both in children and in adults. Both present the same symptoms, with the majority of adults diagnosed with this disorder suffering from these symptoms since childhood. Diagnosing this disorder and psychotherapeutic treatment at an early stage are very important, since it is possible that early treatment could prevent the symptoms from becoming worse during adulthood. A review of the literature on the psychotherapeutic treatment of children with this disorder identified that the psychological technique most frequently used has been Cognitive-Behavioral therapy. However, some studies have identified that there is a low adherence by children receiving this treatment. This resistance occurs due to the use of some techniques that include repetitive exercises, which are often monotonous and also having to note daily tasks, which, for some children, is difficult to perform. Few case studies were identified based on other psychological approaches. No reference was found in analytical psychology and Sandplay therapy for treating children with this disorder. Therefore, this research is the first study to apply Sandplay therapy for such cases. This research was developed using a qualitative-quantitative method, which enabled a qualitative analysis of the verbal expressions and images of each scenario to be made, followed by a quantitative analysis of these data. The therapeutic process was divided into three periods: start, middle and end. An evolutionary line was drawn of the process from the moment the first scenario was made by each subject, and a comparison was made between the three subjects. A comparison between the three cases provides evidence of how the analytic process together with sandplay therapy enables development of consciousness from a more primitive state of identity: the expression and use of symbols; the transformation of defense mechanisms and strengthening of the ego. The psychological structure of each child was transformed and at the end of the psychotherapeutic process there was a remission in their symptoms and they were no longer receiving pharmacological treatment